Micronucleus test on Triturus carnifex as a tool for environmental biomonitoring. (27th September 2014) - Udroiu, I.; Sgura, A.; Vignoli, L.; Bologna, M.A.; D'Amen, M.; Salvi, D.; Ruzza, A.; Antoccia, A.; Tanzarella, C.
Abstract : The amphibian micronucleus test has been widely used during the last 30 years to test the genotoxic properties of several chemicals and as a tool for ecogenotoxic monitoring. The vast majority of these studies were performed on peripheral blood of urodelan larvae and anuran tadpoles and to a lesser extent adults were also used. In this study, we developed protocols for measuring micronuclei in adult shed skin cells and larval gill cells of the Italian crested newt ( Triturus carnifex ). Amphibians were collected from ponds in two protected areas in Italy that differed in their radon content. Twenty‐three adult newts and 31 larvae were captured from the radon‐rich pond, while 20 adults and 27 larvae were taken from the radon‐free site. The animals were brought to the laboratory and the micronucleus test was performed on peripheral blood and shed skins taken from the adults and on larval gills. Samples from the radon‐rich site showed micronucleus frequencies higher than those from the radon‐free site and the difference was statistically significant in gill cells ( P < 0.00001). Moreover, the larval gills seem to be more sensitive than the adult tissues. This method represents an easy (and noninvasive in the case of the shed skin) application of the micronucleus assay that can be useful for environmental studies in situ. Environ. Mol. Mutagen. 56:412–417, 2015. © 2014 Wiley Periodicals, Inc.